Assessment of the application for renewal of authorisation of selenomethionine produced by Saccharomyces cerevisiae CNCM I‐3060 (selenised yeast inactivated) for all animal species. (20th July 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the application for renewal of authorisation of organic form of selenium produced by Saccharomyces   cerevisiae CNCM I‐3060 (selenised yeast inactivated) (Sel‐Plex ® ) for all animal species. In 2006, the FEEDAP Panel delivered an opinion on the safety and efficacy of the additive; subsequently it was authorised in the EU. The evidence provided indicates that the additive currently in the market complies with the conditions of authorisation. No new evidence was found that would make the FEEDAP Panel reconsidering its previous conclusions in the safety for target species, consumers and environment. In particular, the Panel confirms that the use of Sel‐Plex ® in animal nutrition does not pose a risk to consumers provided that the maximum selenium supplementation of 0.2 mg/kg feed from Sel‐Plex ® is not exceeded, yet respecting the maximum total selenium in feed of 0.5 mg/kg. In the context of the current application, the Panel reviewed toxicological studies; based on two repeated‐dose studies on rats and dogs, it is concluded that the toxic potential of Sel‐Plex ® is only related to its selenium content. New data on characterisation of the additive and studies on effects on skin and eyes led the Panel reconsider the safety for the user. The Panel concluded that the additive is hazardous upon inhalation and a likely respiratory sensitiser; owing to the high dusting potential, persons handling the additive are at risk by inhalation. It is considered not irritant to the eyes and skin. A recommendation regarding the denomination of the additive under assessment was proposed by the Panel.